If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (g + -7)(g + 9) = 0 Reorder the terms: (-7 + g)(g + 9) = 0 Reorder the terms: (-7 + g)(9 + g) = 0 Multiply (-7 + g) * (9 + g) (-7(9 + g) + g(9 + g)) = 0 ((9 * -7 + g * -7) + g(9 + g)) = 0 ((-63 + -7g) + g(9 + g)) = 0 (-63 + -7g + (9 * g + g * g)) = 0 (-63 + -7g + (9g + g2)) = 0 Combine like terms: -7g + 9g = 2g (-63 + 2g + g2) = 0 Solving -63 + 2g + g2 = 0 Solving for variable 'g'. Factor a trinomial. (-9 + -1g)(7 + -1g) = 0Subproblem 1
Set the factor '(-9 + -1g)' equal to zero and attempt to solve: Simplifying -9 + -1g = 0 Solving -9 + -1g = 0 Move all terms containing g to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1g = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1g = 0 + 9 -1g = 0 + 9 Combine like terms: 0 + 9 = 9 -1g = 9 Divide each side by '-1'. g = -9 Simplifying g = -9Subproblem 2
Set the factor '(7 + -1g)' equal to zero and attempt to solve: Simplifying 7 + -1g = 0 Solving 7 + -1g = 0 Move all terms containing g to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1g = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1g = 0 + -7 -1g = 0 + -7 Combine like terms: 0 + -7 = -7 -1g = -7 Divide each side by '-1'. g = 7 Simplifying g = 7Solution
g = {-9, 7}
| 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e | | 2x+2=0.50x+11 | | 5a+12=36 | | 3n-5n=3 | | (7x-6)=90 | | 5/7x35 | | 5(2x+6)=-3(4x-1) | | 4(m-2)=14 | | (4x+3)+(-2x+4)=y | | 4.7p+8.7p+2.6p=93.96 | | 18x-36=12x-24 | | 2.2=-log(x) | | -15x+43=-10x+28 | | 47=2+9w | | 3(5y+5)=5y+45 | | 4a+8b=x | | 1/x=7/30 | | 16x+191=8x+127 | | -14x-153=-7x-90 | | -r/3=-100 | | -14+135=-7x+79 | | Y-z=x-y | | 17x+60=9x+36 | | 5/24=10/g | | 4/9a=1/9a-5/6 | | 5n-6=-106 | | 14x-76=8x-40 |